Career Choices Among Individuals with Disabilities in the Gulf Region: Cultural, Religious, Policy, and Socio-Economic Influences: A Literature Review - Maha Al-Hendawi; Esraa Hussein; Fathia Ismail (Societies)
This study explores the multifaceted factors influencing career decisions among individuals with disabilities (IWDs) in the Gulf region, emphasizing the interplay between health and cultural/religious contexts. To examine these complex influences, this review adopts Bronfenbrenner’s Ecological Systems Theory as a guiding framework. This theoretical lens facilitates an in-depth analysis of how personal attributes, religious and cultural beliefs, disability-specific challenges, systemic and environmental barriers, gender-related issues, social networks, transition and teachers’ attitudes, work environment, and government policies interact across multiple levels to shape career choices for IWDs in the Gulf region. Cultural and religious beliefs critically shape both the perceptions and opportunities available to IWDs, reflecting the broader macrosystem influences. By applying this multi-layered approach, this review highlights the need to integrate religious and spiritual considerations into support frameworks to enhance the mental and physical well-being of IWDs as they navigate their career paths. The findings suggest actionable implications for policymakers and practitioners dedicated to improving inclusion and equity in the workforce for individuals with disabilities.